750 Narrative Review of the Morphofunctional Underpinnings and Comprehensive Rehabilitation Strategies for Smartphone-addicted University Students (Balneo and PRM Research Journal, 2025)
The widespread availability of mobile phones has contributed to a high prevalence of digital addiction worldwide. Smartphone addiction or problematic smartphone use (SA/PSU) has become a widespread issue, especially among university students.Due to concerns about SA/PSU and cyber addiction in young people, research has focused on the structural and functional effects on the brain and the behavioral consequences of spending too much time on mobile phones. This review investigates the impact of excessive smartphone use on this demographic group's physical and mental health.MethodsAn advanced search on PubMed based on primary keywords, clustered in syntactic associations looked for academic work focusing on: ((((smartphone addiction) and (problematic smartphone use)) and (students) and (Physical exercises)) and (Physical Activity).The relationship (((smartphone addiction) and (problematic smartphone use) and (systematic review) identified 22 papers, published between 2016 and 2024, 16 of which were during the Covid era and post-pandemic periods (2020-2024).Smartphone overuse-induced alterations in cerebral gray matter were observed in four trials.The beneficial influence of physical activity on smartphone addiction was emphasized in 11 publications (selected 9) identified by the advanced search with the syntactic relationship.DiscussionThe narrative review offers a comprehensive overview of effective strategies for addressing SA/PSU. This includes utilizing exercise and psychological interventions to combat digital addiction.Furthermore, studies have looked into the potential benefits of physical exercise and specific strategies addressing these issues. Engaging in physical activity may help offset the negative effects of SA/PSU, and targeted strategies are necessary for preventing and treating these problems in young people.